Near-Infrared-II Cyanine/Polymethine Dyes, Current State and Perspective - Du, Yijing; Liu, Xiangping; Zhu, Shoujun (Frontiers in Chemistry, 2021)
The development of near-infrared-II (NIR-II) fluorescence imaging has implemented real-time detection of biological cells, tissues and body, monitoring the disease processes and even enabling the direct conduct of surgical procedures. NIR-II fluorescence imaging provides better imaging contrast and penetration depth, benefiting from the reducing photon scattering, light absorption and autofluorescence. The majority of current NIR-II fluorophores suffer from uncontrollable emission wavelength and low quantum yields issues, impeding the clinical translation of NIR-II bioimaging. By lengthening the polymethine chain, tailoring heterocyclic modification and conjugating electron-donating groups, cyanine dyes have been proved to be ideal NIR-II fluorophores with both tunable emission and brightness. This minireview will outline the recent progress of cyanine dyes with NIR-II emission, particularly emphasizing their pharmacokinetic enhancement and potential clinical translation.